Pengaruh Sosial Demografi Terhadap Produktivitas Tenaga Kerja Perempuan Pengrajin Lontar di Desa Bona, Gianyar - Andari, Ni Putu Uti; Aswitari, Luh Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 1, No. 1, November 2012 (pp. 1-60), 2012)
Bali has many center of home industry. The development of home industry is expected to increase local entrepreneurs income and salary of employee. In palm leaf handicrafts, activities done by women. This study aims to determine the factors that impacted to women labour productivity. This research was conducted in the Bona Village Gianyar Regency. The number of sample is 93 which taken purposively. This study uses multiple linear regression analysis. Results showed that the factors that affect women labour productivity were age, work experience and marital status. Education does not affect the productivity. Age is the dominant factor affecting women labour productivity in palm leaf handicrafts in Bona Village.
Keywords: Palm Leaf Handicrafts , Productivity , Women Labour